FORMING MATHEMATICAL IMAGINATION OF PRIMARY SCHOOL STUDENTS USING GAME TECHNOLOGY (ResearchJet Journal of Analysis and Inventions, 2021)
This article discusses the formation of mathematical imagination of primary school students using game technology, the introduction of new information technologies in education, and so on.